Scheduling algorithm for user requirements on cloud computing base on deadline and budget constraints - Ha, Nguyen Hoang; Bình, Nguyễn Thanh (Journal of Computer Science and Cybernetics, 2015)
The goal of the SaaS provider is the most profitable; the user’s goal is to meet requirements as quickly as possible but still within budget and deadline. In this paper, a heuristic ACO (Ant Colony Optimization) is used to propose an algorithm to admission control, then building a scheduling algorithm based on the overlapping time between requests. The goal of both algorithms is to minimize the total execution time of the system, satisfying QoS constraints for all requirements and provide the greatest returned profit for SaaS providers. These two algorithms are set up and run a complete test on CloudSim, the experimental results are compared with sequential and EDF (Earliest Deadline First) algorithms.